Terapia Manual en el dolor crónico por Artritis Reumatoide - Paul Adrián, Chiriboga Murillo (2021)
ABSTRACT The research was developed as a literature review, collecting and analyzing scientific articles related to the main objective. This literature review is related to Manual Therapy and how this technique improved the chronic pain of Rheumatoid Arthritis to determine the efficacy of the treatment. At the same time, this research generates updated information on the application of manual therapy. Thus, it aims to contribute to the knowledge of both professionals and students. Rheumatoid Arthritis is a systematic, autoimmune, progressive, and chronic disease that can cause functional disability. It is characterized by being polyarticular; it follows a predominant affection pattern that causes pain, inflammation, and discomfort. Thus, it affects the peripheral joints such as the fingers, hands, elbows, shoulders, knees, and ankles. Given these discomforts, it is essential to know about Manual Therapy's treatment, mainly because it helps to regain movement and relieves pain in the affected joints, according to the collected information. This research encounters about 150 articles that were located through scientific search engines such as Scielo, PubMed, Word Wide Science, Diane, Elsevier, and Scholar Google. The search was performed in different languages such as English, Chinese, Portuguese, Russian, and Spanish, and its selection was according to the inclusion and exclusion criteria. Pedro scale was chosen for the scientific evaluation, and after the process, 35 articles remained to work. Based on the scientific article analysis, it was concluded that Manual Therapy shows effective results in the treatment of rheumatoid arthritis. Consequently, there is a notable improvement in the patient; it reduces chronic pain, improves range of motion, decreases joint stiffness, increases strength, maintains functionality, and helps the individual in daily life activities. Keywords: Therapy, Manual, Pain, Arthritis, Joints. Reviewed by: Mgs: Sonia Granizo Lara. ENGLISH PROFESSOR. c.c. 0602088890